A Dual‐Functional Ferroferric Oxide/Quantum Dots Theranostic Nanoplatform for Fluorescent Labeling and Photothermal Therapy. (30th April 2021) - Yin, Naiqiang; Li, Peng; Xu, Xiaoliang; Zhu, Lixin
Abstract: A biocompatible, nontoxic theranostic nanoplatform consisting of mesoporous silica‐coated ferroferric oxide (Fe3 O4 ) and Mn‐doped ZnS‐ZnS quantum dots (QDs) is synthesized via a layer‐by‐layer method. Transmission electron microscopy, X‐ray diffractometer, magnetometry, and fluorophotometer are employed to characterize the nanoplatform. The nanoplatform exhibits excellent superparamagnetic, fluorescent, and light absorption properties. The template method is introduced to form a mesoporous silica structure on the nanoplatform, lowering the mass of the nanoplatform and effectively promoting the absorption efficiency of the incident light compared with the traditional silica layer. In addition, after endocytosis of the nanoplatform, cancer cells are easily detected under a fluorescence microscope because of the excellent fluorescent behavior of QDs. Moreover, in vitro experiments confirm that nanoplatform possesses perfect photothermal effect to destroy tumor cells under laser irradiation. Therefore, ferroferric oxide/QDs nanoplatforms, combined with the functions of fluorescent labeling and photothermal therapy for cancer cells, are expected to be a promising biopotential material in the field of diagnosis and treatment. Abstract : A ferroferric oxide/quantum dots (QDs) theranostic nanoplatform is designed, realizing the functions of targeted labeling and photothermal therapy for cancer cells. Mesoporous silica is introduced to reduce the mass density of the nanoplatform, improving the structural stability and dispersibility of nanoplatform. Moreover, the porous structure of the silica favors the penetration of irradiation light, improving the absorption efficiency of the nanoplatform.